STRUCTURAL AND CULTURAL ASPECTSOF COMPLIMENT RESPONSES IN MACEDONIANAND ALBANIAN IN COMPARISON TO ENGLISH (Journal of Contemporary Philology, 2018)
This paper investigates compliments and compliment responses in order to reveal cultural differences and similarities between Macedonian, Albanian and English language through the use of this speech act. Thе main hypothesis is that there are similarities between Macedonian and Albanian culture as they belong to a broader cultural milieu of the Balkans. The research is based on two corpоra: the first corpus consists of everyday life situations (CELS or KRS) and it contains 100 compliment exchanges and the second corpus is created through a Discourse Completion Test (CDCT or KPS) and it contains 1320 examples. Compliment responses are examined with the aim to see how much they reflect the cultural background of Macedonian and Albanian nation. A particular attention is paid to Brown and Levinson’s Politeness theory and to the notion of Face in the frames of which compliment responses are examined with the aim to learn how these two cultures perceive politeness and whether they are more prone to self-praise or modesty. Compliment responses are also examined as potential Face-threatening or Face-saving acts. Nationality, sex and age of the respondents are taken into consideration as factors that influence compliment responses.
Keywords: speech acts; politeness theory; face; face-threatening acts; compliments; compliment responses